Effects of pollutants in alkali/surfactant/polymer (ASP) flooding oilfield wastewater on membrane fouling in direct contact membrane distillation by response surface methodology. (November 2021) - Yan, Xiaoju; Wang, Guodong; Ma, Cong; Li, Junyu; Cheng, Shirong; Yang, Chengyu; Chen, Lin
Abstract: The characteristic pollutants in alkali/surfactant/polymer (ASP) flooding oilfield wastewater are complex [e.g., NaCl, sodium dodecyl sulfate (SDS), petroleum, and polyacrylamide (PAM)]; thus, membrane distillation (MD) applied to treat this wastewater will be fouled and wetted easily. In this study, response surface methodology (RSM) was used to analyze the effects of pollutant interactions in ASP flooding oilfield wastewater on membrane fouling. The response model showed quantitative relationships between the membrane flux and the pollutant concentrations. The analysis of variance ( p -value of the model < 0.0001, p -value of lack of fit > 0.05, R 2  = 0.9750 and R 2 adj  = 0.9500) showed that the regression equation fit the empirical data well. The results also indicated that the interactions of pollutants (NaCl and SDS; petroleum and PAM) had significant influence on the flux decline in the simulated ASP flooding oilfield wastewater. The characterization of Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) revealed that the MD membrane was fouled by simulated ASP flooding oilfield wastewater to a certain degree. Moreover, the membrane flux was restored to 86.9% after hydraulic cleaning. Graphical abstract: Image 1 Highlights: Effects of ASP wastewater pollutant characteristics on MD were investigated by RSM. The RSM model predicted the decline of MD permeate flux well. Hydraulic cleaning could remove most of the pollutants deposited on membrane.